The Influence of Corporate Social Responsibility on Employee Performance with Organizational Commitment as Mediation: Study Of Bank Lampung Employees - HERMAN, Kharisma Deslia; ERLINA, Rr; MARDIANA, Nova (International Journal of Environmental, Sustainability, and Social Science, 2024)
This research is to determine the effect of CSR on employee performance, CSR on organizational commitment, organizational commitment on employee performance, and is mediated by organizational commitment. The number of samples in this research is 210 samples, testing using the SEM test using the SEM-PLS analysis tool, the findings in this research There is that Corporate Social Responsibility (CSR) have a significant positive influence on Employee Performance. In addition, CSR also have a significant positive influence on Organizational Commitment. Organizational Commitment has a significant positive influence on Employee Performance. The latest findings show that Employee Performance has a significant positive influence, with Organizational Commitment as a mediating variable. the results about CSR showed that the lowest average scores were recorded on the assessment or evaluation indicators. To anticipate the spread of a similar response, companies need to identify the causes of this response. In the results of respondents, the lowest indicator of employee performance is the work quality indicator. Organizations must delve deeper into understanding the reasons behind the subpar quality of work observed within their operations. Within the spectrum of organizational Commitment, it is evident that the normative commitment indicator scores the least. Organizations need to cultivate a culture where employees feel intensely loyal. This can be done through employee development programs, appropriate incentives, and a supportive work environment.